Long-term survival and health-related quality of life in patients with severe acute respiratory distress syndrome and veno-venous extracorporeal membrane oxygenation support - Rilinger, Jonathan; Krötzsch, Klara; Bemtgen, Xavier; Jäckel, Markus; Zotzmann, Viviane; Lang, Corinna N.; Kaier, Klaus; Dürschmied, Daniel; Supady, Alexander; Bode, Christoph; Staudacher, Dawid; Wengenmayer, Tobias (Critical care, 2021)
There is limited information about the long-term outcome of patients suffering from acute respiratory distress syndrome (ARDS) supported with veno-venous extracorporeal membrane oxygenation (VV ECMO). Most studies focused on short- to mid-term follow-up. We aimed to investigate long-term survival and health-related quality of life (HRQL) in these patients.